LAW IMPLEMENTATION IN SPORT - Mexhid Krasniqi; Afrim Berisha; Adrm Nura; Blerim Sylejmani (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
This work offers a short review of sports marketing and management. It presents different ways of advertising some products either in sports events or throng electronic mediums. In addition, it reviles different aspects of the influence that politics and discrimination has on sport as well as the way of solving eventual arguments of any kind.